2018
DOI: 10.1108/inmr-02-2018-004
|View full text |Cite
|
Sign up to set email alerts
|

Motivations of crowdsourcing contributors

Abstract: Purpose This study aimed at analyzing the factors that induce the intention of contribution by participants in crowdsourcing initiatives. Design/methodology/approach This study is an explanatory investigation using a quantitative approach. In the second stage, an exploratory study was carried out. Data were obtained through online questionnaires available to the contributors of two platforms, and results were obtained from a regression analysis. Findings The results revealed a greater importance given by p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 23 publications
0
11
0
1
Order By: Relevance
“…It is important to note that crowdsourcing relies on individuals whom are paid a relatively small fee for service. Prior studies have found many crowdsourcing participants intrinsically motivated by altruism and not extrinsically motivated through financial incentives, which is reflected in the socioeconomic representation of our participants, with the majority (51.8%) earning more than $40 000 per year (19.1% earning > $80 000). Despite the intrinsic motivation of many crowdsourcing participants, it is important for the medical community to strive for ethical working conditions for research participants utilized in all studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is important to note that crowdsourcing relies on individuals whom are paid a relatively small fee for service. Prior studies have found many crowdsourcing participants intrinsically motivated by altruism and not extrinsically motivated through financial incentives, which is reflected in the socioeconomic representation of our participants, with the majority (51.8%) earning more than $40 000 per year (19.1% earning > $80 000). Despite the intrinsic motivation of many crowdsourcing participants, it is important for the medical community to strive for ethical working conditions for research participants utilized in all studies.…”
Section: Discussionmentioning
confidence: 99%
“…The use of crowdsourcing platforms, such as Amazon's Mechanical Turk (MTurk) Prime, provides researchers access to difficult to reach populations and allows participants to answer questions that have the potential to benefit society at large more significantly than smaller cohort studies given the generalizability. Individuals who participate in these crowdsourcing platforms are primarily intrinsically motivated through altruism and have a desire to contribute to society . As a field, it is important to transition our research methods as technology advances and to utilize approaches that allow more members of society a platform to let their voices be heard.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In many cases, the rewards system is used as a tool to enhance the employee"s performance. The main reward system implemented is an increase in salaries and wages which is a monetary aspect of motivation (Pinto & dos Santos, 2018). Every employee needs a good salary package along with other benefits such as bonuses, allowances, medical claims, etc.…”
Section: Impact Of Reward Systems On Employee Motivationmentioning
confidence: 99%
“…When it comes to non-monetary rewards, the first thing is that learning and training opportunities are provided to employees who do not have much knowledge about their area of expertise because this is the best time to improve and motivate employees sitting at their homes which is quite difficult during the normal busy working hours. The second thing is employees are given recognition as they attend meetings and show their best efforts to finish the work during such hard times (Pinto & dos Santos, 2018).…”
Section: Impact Of Reward Systems On Employee Motivationmentioning
confidence: 99%